Classroom quality and children's social skills and problem behaviors: dosage and disability status as moderators - Aguiar, A.; Aguiar, C.; Cadima, J.; Correia, N.; Fialho, A. (Early Childhood Research Quarterly, 2019)
Multiple studies have reported associations between early childhood education (ECE) quality and dosage and children’s social and behavior development, with some suggesting that this association may be stronger for specific groups of children. In this study, we examined the association between classroom quality and children’s social skills and problem behaviors, as reported by ECE teachers, as well as the moderating effects of ECE dosage and children’s disability status. Participants were 222 children (Mage = 63.75, SD = 7.77), including 180 typically developing (90 boys) and 42 children with disabilities (29 boys), from 44 inclusive classrooms in the Metropolitan Area of Lisbon, Portugal. Our results indicated that children’s social skills and behavior problems were not directly associated with observed classroom quality domains. However, lower classroom organization predicted lower social skills and higher externalizing behavior at higher number of months with the lead teacher; and instructional support predicted increased social skills for children with disabilities. Days absent from school predicted lower social skills. Overall, our results suggest that diverse types of dosage influence teacher’s reports of social and behavioral outcomes in different ways.